Vitamin D, a steroid hormone, from theory to practice - Bičíková, M; Máčová, L (Physiological research, 2023)
Recently deceased professor Luboslav Stárka was a world-renowned doctor who devoted his whole life to the study and therapeutic use of steroids, and was particularly interested in vitamin D. He knew from his own experience and from deep knowledge that this vitamin, one of the oldest steroids in development, must have a number of effects in addition to the undeniably positive effects on bones. He commissioned our task force to address the issues surrounding vitamin D, leading to years of studies with robust results made possible by the use of chromatography coupled with mass spectrometry (LC-MS), a so-called gold standard of measurement that is a cornerstone of recent scientific studies. This led to a whole series of scientific publications, the aim of which was to point out the possibility of using the abilities of vitamin D and thus also the gift that nature has given us.
Keywords: steroidy; hormony; Chromatography, Liquid; Humans; chromatografie kapalinová; mužské pohlaví; Male; lidé; vitamin D; Steroids; Vitamins; vitaminy; Vitamin D; Hormones